2022
DOI: 10.3390/ijerph19158886
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Spatial Modeling of Diabetes and Hypertension: Results from the South Africa General Household Survey

Abstract: Determining spatial links between disease risk and socio-demographic characteristics is vital in disease management and policymaking. However, data are subject to complexities caused by heterogeneity across host classes and space epidemic processes. This study aims to implement a spatially varying coefficient (SVC) model to account for non-stationarity in the effect of covariates. Using the South Africa general household survey, we study the provincial variation of people living with diabetes and hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Of the total of 52 studies, 26 (50.0%) were on infectious diseases, 11 (21.1%) on malaria [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], 8 (15.3%) on Dengue fever [ 40 , 41 , 42 , 43 , 44 , 45 ], 4 (7.6%) on HIV [ 46 , 47 , 48 , 49 ], and 3 (5.7%) on TB [ 50 , 51 , 52 ]. Overall, 10 (19.2%) studies were on chronic diseases [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], 8 (15.5%) on maternal and child health [ 63 , 64 , 65 , 66 ], 3 (5.7%) on nutrition [ 67 , 68 , 69 ] and 5 (9.6%) were applied to other health-related outcomes [ 58 , 70 , 71 , 72 , 73 ]. Most of the studies (42, 80.7%) used an ecological study design [ 30 , 31 , 33 , 34 , 37 , 38 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the total of 52 studies, 26 (50.0%) were on infectious diseases, 11 (21.1%) on malaria [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], 8 (15.3%) on Dengue fever [ 40 , 41 , 42 , 43 , 44 , 45 ], 4 (7.6%) on HIV [ 46 , 47 , 48 , 49 ], and 3 (5.7%) on TB [ 50 , 51 , 52 ]. Overall, 10 (19.2%) studies were on chronic diseases [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], 8 (15.5%) on maternal and child health [ 63 , 64 , 65 , 66 ], 3 (5.7%) on nutrition [ 67 , 68 , 69 ] and 5 (9.6%) were applied to other health-related outcomes [ 58 , 70 , 71 , 72 , 73 ]. Most of the studies (42, 80.7%) used an ecological study design [ 30 , 31 , 33 , 34 , 37 , 38 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 10 (19.2%) studies were on chronic diseases [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], 8 (15.5%) on maternal and child health [ 63 , 64 , 65 , 66 ], 3 (5.7%) on nutrition [ 67 , 68 , 69 ] and 5 (9.6%) were applied to other health-related outcomes [ 58 , 70 , 71 , 72 , 73 ]. Most of the studies (42, 80.7%) used an ecological study design [ 30 , 31 , 33 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies modeling the relationships between these diseases and socioeconomic risk factors through GWR techniques have also found regional variations. Ogunsakin ( 43 ) revealed that educational status had different effects across provinces of South Africa when investigating diabetes and hypertension. Park et al ( 44 ) addressed the hypertensive disease mortality in South Korea and found that the effects of socioeconomic status were only consistent in some regions of the country.…”
Section: Discussionmentioning
confidence: 99%